VALUASI EKONOMI OBJEK WISATA GUA KRISTAL DI DESA BOLOK KECAMATAN KUPANG BARAT KABUPATEN KUPANG - Feronika Tosi; Nikson Tameno; Aldarine Molidya (E-Jurnal Ekonomi Pembangunan, 2024)
This study aims to determine the economic valuation of the crystal cave tourist attraction. This research is quantitative research with multiple regression analysis to determine the factors that influence the number of tourist visits. Meanwhile, to determine the economic value of the crystal cave tourist attraction is shown through consumer surplus seen from travel costs. The sample of tourists was determined using sampling techniques with the number of samples used as many as 97 respondents. The results showed that the variable that had a significant effect on the variable number of visits was the distance variable. The economic value of the crystal cave tourist attraction reached IDR 463,994,025.61. The magnitude of the economic value of the crystal cave tourist attraction is expected for managers to improve the management of crystal cave tourism by improving and making facilities to provide more satisfaction to visitors.